(untitled) (LACCEI, 2024)
Currently, particulate matter emissions have a profound influence on population health, atmospheric visibility, and the climate of a place worldwide. Therefore, in this systematic review we analyzed the atmospheric dispersion of particulate matter (PM2.5 and PM10) and its significance to the environment, according to scientific journals of the last 10 years worldwide. Theses and articles from journals such as Scopus, Dialnet, ScienceDirect, etc taking into account the period 2012-2022 and the Spanish and English languages were used. Articles were included that contained information and results that contributed to the research where they showed the appropriate modeling. As a result, the most used atmospheric dispersion model is AERMOD, and in several cities PM emissions do not comply with the ECAs of the country or the WHO. Among the limitations was the small number of articles focused on PM because most of them mention particulate matter as an additional pollutant. We conclude that it is important to have knowledge about PM emissions that occur near urban areas, in order to have a perspective on air quality and, if it is poor, to implement solutions to reduce emissions.